Thermodynamics of metal-insulator systems - Kasl, Charles. (My University, 1996)
The properties-of systems which undergo a metal-insulator (MI) transition are currently being extensively studied. Both the transport and thermodynamic properties of these MI systems show interesting behaviour, particularly near the MI transition. A complete theory to describe MI systems does not yet exist. In the present work the focus is on the thermodynamic properties of MI systems, in particular on the specific heat and susceptibility. The thermodynamic properties in the absence of a magnetic field are now well understood, with models such as the two-fluid model giving a good account of the behaviour. In finite magnetic fields the thermodynamic properties are even more interesting and varied. It is the aim of the present work to develop and test models to explain the effects of applying magnetic fields to MI systems. The focus is mainly on phosphorous doped silicon, and the results are gratifying. The theory should, however, also apply to other similar MI systems.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science.
Keywords: Metal-insulator transitions.; Thermodynamics.